THE CORRELATION BETWEEN STUDENTS’ SIMPLE PAST TENSE MASTERY AND THEIR ABILITY IN TRANSLATING NARRATIVE TEXT AT THE FIRST YEAR OF SMA NEGERI 5 PAREPARE - Masriani; amzah (Prodi Tadris Bahasa Inggris STAIN Parepare (IAIN Parepare), 2018)
This research aims at to see the correlation between students? simple past tense mastery and their ability in translatingnarrative text in the first year of SMA Negeri 5 Parepare. The results of the research are useful for the teacher and students. The teacher will aware that it is important to teach simple past tense to the students before asking to translate the narrative text and the students also can be easier translate the narrative text when they master in the simple past tense. The subject of this research is X Mia 4 class which is consisted of 22 students. The sample was taken by using purposive sampling. The design in this research was descriptive quantitative by giving a grammar test and translation test. Grammar test consists of 15 numbers multiple choices about simple past tense and students were given a narrative text to translate. The result of the tests showed that there is a correlation between students? simple past tense mastery and their ability in translating narrative text. Students who had a high score in simple past also had a high score in translating narrative text but students who had a low score in simple past tense also had a low score in translating narrative text.